Differential Diagnosis of Multiple System Atrophy-Parkinsonism and Parkinson's Disease Using α-Synuclein and External Anal Sphincter Electromyography - Cao, Zhentang; Wu, Yufeng; Liu, Genliang; Jiang, Ying; Wang, Xuemei; Wang, Zhan; Feng, Tao (Frontiers in Neurology, 2020)
Background and aim: The differential diagnosis of multiple system atrophy-parkinsonism (MSA-P) and Parkinson’s disease (PD) is difficult. We aim to provide a new method to distinguish MSA-P from PD by combining biofluid marker with electrophysiology marker. Methods: The saliva sample were obtained from 16 MSA-P and 26 PD patients. The XYCQ EV Enrichment KIT was applied to extract extracellular vesicles (EVs) from saliva. Salivary EVs α-syn levels, including total α-syn (α- synTotal), oligomeric α-syn (α-synOlig) and phosphorylated-ser129 α-syn (α-synPS129), were measured by Electrochemiluminescence assays. We performed multi-motor unit potential (MUP) analysis of external anal sphincter (EAS) in all participants. The duration, phase, amplitude and satellite potential of EAS-EMG were collected. The diagnostic value of α-syn in salivary EVs, EAS-EMG for MSA-P were determined by Receiver operator characteristic curve. Results: The α-synTotal in salivary EVs was lower in MSA-P than in PD (P=0.003). There was no significant difference in α-synOlig and α-synPS129. α-synTotal 4.46 pg/ng distinguished MSA-P from PD with area under the curve (AUC): 0.804. Compared with PD, the duration, phase and satellite potential of EAS-EMG in MSA-P were increased (P=0.002, 0.008, 0.001). There was no significant difference in amplitude. ROC was showed the duration (AUC: 0.780), phase (AUC: 0.751) and satellite potential (AUC: 0.809) had diagnostic value between MSA-P and PD. The combination of α-synTotal in salivary EVs and EAS-EMG (including duration, phase and satellite potential) could efficiently distinguish MSA-P from PD (sensitivity of 100%; specificity of 86%; AUC: 0.901). Conclusion: The study suggested the combination of α-synTotal in salivary EVs and EAS-EMG could help efficiently distinguish MSA-P from PD.